Implementation of Curriculum Management To Improve Teacher’s Performance - Suryani, Suryani; Ahmad, Syarwani; Puspita, Yenny (Yayasan Sembilan Pemuda Indonesia, 2024)
The general aim of this research is to describe the implementation of curriculum management in improving teacher performance at SMP Negeri 4 Air Sugihan, Ogan Komering Ilir Regency. Meanwhile, the specific objectives of this research are as follows: 1) Describe the implementation of curriculum management planning in improving teacher performance; 2) Describe the implementation of curriculum management in improving teacher performance; 3) Describe the implementation of curriculum management supervision in improving teacher performance; 4) Describe the implementation of curriculum management evaluation in improving teacher performance. This research is a qualitative descriptive study and was carried out at SMP Negeri 4 Air Sugihan, Ogan Komering Ilir Regency with 10 teachers as research informants. Data collection techniques were carried out through interviews, observation, and documentation studies. Data analysis techniques use data reduction, data presentation, and data verification. The results of this research show that: 1) the implementation of curriculum planning in improving teacher performance has been carried out well; 2) the implementation of curriculum management in improving teacher performance has been carried out well; 3) implementation of curriculum management supervision in improving teacher performance has been carried out well; 4) implementation of curriculum management evaluation in improving teacher performance has been carried out well.